Computer assisted diagnosis of benign bone tumours - Samardziski, Milan (Radiology and oncology (Ljubljana), 2004)
Background. The aim of this study is to determine the correlation between computer-assisted diagnosis (CAD) of benign bone tumours (BBT) and their histological type. Patients and method. Altogether 120 patients were included in two groups. The retrospective group comprised 68 patients in whom the histological type of BBT was known prior to computer analysis. The prospectivegroup comprised 52 patients in whom the histological type of BBT was unknown prior to computer analysis. Computer program was efficient and easy to use. Results. Average percent of histological type confirmed with CAD in the retrospective and prospective groups was 72.06% and 76.92%, respectively. Histological confirmation of CAD in specific BBT was 91.42% for enchondroma, 96.15% for osteoid-osteoma, and 98.08% for osteochondroma. Significantly lower percentage of CAD confirmation of fibroma, chondromixoid fibroma, osteoclastoma, desmoplastic fibroma and osteobalstoma due to their adverse biological character or complex anatomic localization is understandable. Conclusions. The results speak in favour of the assumption that computer assisted diagnosis of bone tumours program may improve the diagnostic accuracy of the examiner.
Keywords: Bone Neoplasms; Diagnosis; Diagnosis, Computer-Assisted; diagnostika; Diagnostika z računalnikom; Fibrom; Fibroma; Hemangiom; Hemangioma; kosti; Kostne novotvorbe; Lipom; Lipoma; neoplazme; Osteoblastom; Osteoblastoma; Osteochondroma; Osteohondrom; Osteom; Osteoma; Pathology; Radiography; rak (medicina)